Senescence marker protein30 protects lens epithelial cells against oxidative damage by restoring mitochondrial function. Issue 5 (2nd May 2022) - Teng, He; Hong, Yaru; Cao, Jingjing; Li, Hui; Tian, Fang; Sun, Jing; Wen, Kai; Han, Guoge; Whelchel, Amy; Zhang, Xiaomin; Li, Xiaorong; Dong, Lijie
ABSTRACT: Etiology and pathogenesis of age-related cataract is not entirely clear till now. Senescence marker protein 30 (SMP30) is a newly discovered anti-aging factor, which plays an important role in preventing apoptosis and reducing oxidative stress damage. Mitochondria are located at the intersection of key cellular pathways, such as energy substrate metabolism, reactive oxygen species (ROS) production and apoptosis. Oxidative stress induced by 4-hydroxynonenal (4-HNE) is closely related to neurodegenerative diseases and aging. Our study focused on the effect of SMP30 on mitochondrial homeostasis of human lens epithelial cells (HLECs) induced by 4-HNE. Western blots and qPCR were used to compare the expression of SMP30 protein in the residual lens epithelial cells in the lens capsule of age-related cataract (ARC) patients and the donated transparent lens capsule. On this basis, SMP30 overexpression plasmid and SMP30 shRNA interference plasmid were introduced to explore the effect of SMP30 on the biological behavior in HLECs under the condition of oxidative stress induced by 4-HNE through immunohistochemistry, ROS evaluation, metabolic spectrum analysis and JC-1 fluorescence measurement. Given that Nuclear Factor erythroid 2-Related Factor 2 (Nrf2)/Kelch Like ECH Associated Protein 1 (KEAP1) signaling pathway is the most important antioxidant stress pathway, we further analyzed the regulatory effect of SMP30 by WB to explore its molecular mechanism. Our study indicated that SMP30 may inhibit ROS accumulation, restore mitochondrial function, activate Nrf2/Keap1 signaling pathway, therefore protecting lens epithelial cells from oxidative stress-induced cell damage. Graphical abstract: uf0001